Evropská správněprávní integrace - Šmíd, Martin (Univerzita Pardubice, 2009)
Paper deals with European administrative law or with European integration on the field of administrative law. Concrete topics are: the administrative law of European Union, administrative law of Council of Europe and so-called europeization of administrative law. The paper tries to answer the question, if next integration of administrative law would be suitable (or necessary) or it would be better to solve this problem within the scope of member states.
Keywords: European Union; Council of Europe; administrative law; European administrative space; European Integration